A new Source on the Relationship between Hulun Buir and Outer Mongolia in 1912—1915 - B. D. Tsybenov (Научный диалог)
A little-known source — the manuscript “Historical information on the fragility of the political situation of Hulunbuir”, stored in the State Archives of the Irkutsk region is considered. Description of the manuscript, clarification of its dating, determination of the probable source base was performed by the author of the article. A comparative analysis of the historical facts presented in the manuscript was carried out. It was found that in the first two sentences the anonymous author outlined the essence of the uncertain situation that developed with the annexation of Hulun Buir to Outer Mongolia in 1912. Other components of the text are characterized: little-known information about the trip to Urga of the Bargut lama Lobsanchjamba and then about the visit of the delegation of Hulun-Buir; data on the meeting of the delegates with the Russian consul V. F. Lyuba and a description of his reaction to the fact of the annexation of Hulun-Buir to Outer Mongolia; finally, it is said about the disappointment of the ruler of Hulun-Buir — Shenfu, who realized the dependence of Hulun-Buir on the dependent, in turn, Outer Mongolia, etc. An analysis of the contents of the last page of the manuscript allows us to conclude that part of the Hulunbuir officials, close to the Manchus, expressed open dissatisfaction with the situation. The author of the article suggests that some of the Daurian officials, unlike the Barguts, who sincerely believed in the creation of a unified Mongolian state, tended to restore the Manchu dynasty and were unhappy with the unclear future of Hulun Buir.